Made for China Success Strategies From China's Business Icons - Nothhaft, Christian (Springer International Publishing, 2018)
This book shares unique perspectives on the successful global evolution and future ambitions of Chinese consumer companies. It presents an unprecedented collection of one-on-one interviews with some of the most influential leaders in China, whose companies offer diverse products and services. Further, the book offers future business leaders encouragement and guidance on how to ride the consumer wave in China. It also investigates some of the foremost current trends, revealing the best opportunities for companies to succeed on the Chinese market. Written by a successful business leader, this book is a timely must-read for anyone seeking to understand Chinese consumers, the Chinese market and what makes Chinese entrepreneurs tick - helping them learn how to do business "Made for China".